Five Dimensional Bianchi Type-I Anisotropic Cloud String Cosmological Model With Electromagnetic Field in Saez-Ballester Theory - Daimary, Jagat; Roy Baruah, Rajshekhar (Frontiers in Astronomy and Space Sciences, 2022)
Within the context of Saez-Ballester's theory, we explored the interaction of a five-dimensional Bianchi type-I anisotropic cloud string cosmological model universe with an electromagnetic field. With an electromagnetic field, the energy-momentum tensor is assumed to be the sum of the rest energy density and string tension density in this paper. We use the average scale factor as an integrating function of time to get the exact answers to Saez-Ballester equations. The dynamics and physical parameters of the model are also examined.